ANALISIS TENTANG PEMAHAMAN IBADAH MENURUT MAZMUR 50 PADA MAHASISWA STAKN KUPANG - Marsi Bombongan Rantesalu (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2019)
Worship is a basic need for every Christian to draw closer to God. Therefore we need a correct understanding of true worship. This study looks at the level of understanding of students of STAKN Kupang about true worship, that the true worship based on Psalm 50: 1-23 is giving thanks, paying vows, crying out, and living according to God's provision. This study uses a combination of research types. The qualitative method (exegesis) is carried out to get the indicators to be measured. Then proceed with a quantitative approach in the form of a survey to measure the level of student understanding of worship. The results showed that the price of t count = 19.576 and the cost of the t table for a one-tail test with DK 142 = 0.65566. The results of the calculation of the level of understanding of students of STAKN Kupang Semester V regarding the concept of worship, according to Psalm 50: 1-23, is 87.3%.